Penyelidikan Tanah Menggunakan Metode Uji Sondir Di Universitas 17 Agustus 1945 Surabaya - Irgi Rangga Prayoga; Mohammad Chilmi Zakariyah; Priangga Surya Maulana; Ahmad Moh Wildanul Abror; Dika Ayu Safitri (International Forum of Researchers and Lecturers, 2024)
Cone Penetration Test (CPT) is a method designed to determine and test the strength of soil layers quickly and is one of the most widely used testing methods. The aim of this research is to determine the resulting bearing capacity and determine the hard soil layers on the Padhang-Padhang campus of West Sulawesi University using the Cone Penetration Test (CPT) or Sondir field testing tool. The method used in this research is the literature study method and direct testing in the field. From the results of this test, the Cone Penetration Test (CPT) data from 1 test point was processed and analyzed using Microsoft Excel 2019 software. The results of data processing and analysis were the maximum cone pressure (qc) value and the maximum number of sticking resistances (JHP), namely 650 kg/cm at a depth of 12.60 meters and 2496.00 kg/cm² at a depth of 15.00 meters. The maximum friction ratio (Rf) of 0.11% is at a depth of 14.00 meters, while the maximum Sticking Resistance Pressure (fs) value of 110 kg/cm² is at a depth of 14.00 meters.